Genetic structure of Spanish wild populations of Castanea sativa as measured by isozyme analysis - Fernández-López, J.; Monteagudo, A. B. (Forest Systems, 2010)
The genetic variability within and among 17 wild Spanish chestnut stands was examined by isozyme analysis, with the goals of describing their geographic structure and designing conservation and management strategies. Measures of genetic diversity such as allelic richness, heterozygosity, polymorphism, F-statistics, D-statistics, gene flow, clustering using Nei’s genetic distances and a method based on an Monte Carlo Markov Chain algorithm and the contributions of each stand to diversity and allelic richness were all used. Wild Spanish chestnut populations displayed heterogeneity of allele frequencies between them, high levels of genetic diversity and high differentiation (Fst = 0.15) compared with populations from other western European countries such as France and Italy. The two clustering methods allowed the identification of three clusters: a Mediterranean cluster, a northern Spanish cluster and the southern Galician cluster. The highest heterozygosity and allelic richness were found in the North, especially in the southern Galician cluster. Several areas can be recommended for inclusion in the network of Conservation Units: Fraga de Catasós, representing the southern Galician cluster; Fragas do Eume, representing the northern Spanish cluster; and Hervás or El Tiemblo, representing the Mediterranean cluster.